Phosphoinositide Recognition Sites Are Blocked by Metabolite Attachment - Kervin, Troy A.; Wiseman, Brittany C.; Overduin, Michael (Frontiers in Cell and Developmental Biology, 2021)
Membrane readers take part in trafficking and signaling processes by localizing proteins to organelle surfaces and transducing molecular information. They accomplish this by engaging phosphoinositides (PIs), a class of lipid molecules which are found in different proportions in various cellular membranes. The prototypes are the PX domains, which exhibit a range of specificities for PIs. Our meta-analysis indicates that recognition of membranes by PX domains is specifically controlled by modification of lysine and arginine residues including acetylation, hydroxyisobutyrylation, glycation, malonylation, methylation and succinylation of sidechains that normally bind headgroups of phospholipids including organelle-specific PI signals. Such attachments of metabolites to lipid binding elements are named MET-stops here to highlight their roles as erasers of membrane reader functions. These modifications are concentrated in the membrane binding sites of half of all 49 PX domains in the human proteome and correlate with phosphoregulatory sites, as mapped using the Membrane Optimal Docking Area (MODA) algorithm. As these motifs are mutated and modified in various cancers and the responsible enzymes serve as drug targets, the discovery of MET-stops as a widespread inhibitory mechanism may aid in the development of diagnostics and therapeutics aimed at the readers, writers and erasers of the PI code.